Public policies governing the Information Society - Angela López; Fernando Tricas (Netcom)
One or two false hypotheses are rebutted, those that give so much importance to virtual space that they undervalue or ignore the political, economic and cultural elements that shape the physical-social space. This article, however, maintains the hypothesis that the physical-social space, collective action and interaction between the social players are essential for local development, calling for solid and decisive public policies that will develop the ICTs and involve the social and economic players on the one hand, and citizens in general on the other, in advances of technical knowledge and in the trend towards universalisation of this knowledge. So, we explain the European and Spanish public policies that are helping to spread the use of ICTs and remove the digital divide between the more advanced and the less developed social sectors.